Evaluating community participation in planning decision-making in Iskandar Malaysia: Thematic analysis of public planner's perception - Khalid, Zanudin; Ibrahim, Ngah; Siti Hajar, Misnan (2019)
The purpose of this study is to evaluate the effectiveness of community participation in planning decision-making in Iskandar Malaysia. The metropolitan region consists of four local planning authorities that are responsible for governing the spatial planning in the region. Rhetorically, effective community participation helps the local planning authority in making better planning decision, hence provided a sustainable and quality living environment to the community. Thus, it leads to the questions; what constitutes to the effectiveness of community participation in the planning process? To what extent does the current participatory avenue offer a genuine opportunity to the community to incorporate their interest in the planning decision? This phenomenological study used thematic analysis to evaluate the insight postulated by selected public planners which gained through a series of in-depth interview. Following the 12 interviews performed; a total of 37 themes and 68 sub-themes are transpired. A table is used to illuminate the factors that influence the effectiveness of the participatory process in Iskandar Malaysia. The findings suggested that public planners in Iskandar Malaysia believed the effectiveness of community participation in the region is significantly associated with the operational than the structural and cultural dimensions of the process.